Projecting climate change impacts on hydrological processes on the Tibetan Plateau with model calibration against the glacier inventory data and observed streamflow - Zhao, Qiudong; Ding, Yongjian; Wang, Jian; Gao, Hongkai; Zhang, Shiqiang; Zhao, Chuancheng; Xu, Junli; Han, Haidong; Shangguan, Donghui (Journal of hydrology (Amsterdam), 2019)
•A VIC-CAS model, coupled with glacier melting and evolution schemes, was developed.•Good model performances were obtained through a two-stage calibration strategy.•We systematically assessed the runoff and glacier responses to future climate change.•Increased rainfall runoff is the dominant cause of the future streamflow increase. Analyzing the impacts of climate change on hydrology and future projections of water supplies is fundamental for the efficient management and planning of water resources in large river systems on the Tibetan Plateau (TP), which is known as the “water tower of Asia.” However, large uncertainties remain in the projections of streamflow and glaciers in these cryospheric catchments due to great uncertainties in climate change projection and modeling processes. In this work, we developed an extended Variable Infiltration Capacity (VIC) macroscale hydrological model (named VIC-CAS), which was coupled with glacier melting and glacier evolution schemes. A two-stage calibration procedure that used glacier inventory data and the observed streamflow was adopted to derive the model parameters. The calibrated VIC-CAS model was then used to assess the future change in glaciers and runoff using downscaled climate model data in the upstream regimes of the Yellow, Yangtze, Mekong, Salween, and Brahmaputra rivers on the TP. The results indicated that both temperature and precipitation were projected to increase, resulting in a greater than 50% decline of the glacier area by the end of the 21st century in the five catchments. Glacier runoff was already beyond its tipping point at the beginning of the 21st century with a greater than 20% loss of the glacier area except in the upstream of the Yangtze River, where glacier runoff was projected to decrease after the 2030 s. Annual streamflow was projected to increase significantly as a result of increased rainfall-induced runoff, compensating for the reduced glacier/snow melt water in the five major upstream river basins. The increasing rate of warm season streamflow was clearly less than that of annual runoff. A negative trend in warm season streamflow was expected if precipitation did not sufficiently increase. The annual hydrograph remained largely unchanged, except in the upstream of the Yellow River, where peak streamflow was predicted to occur 1 month earlier because of the earlier snowmelt and greater rainfall/precipitation ratio from May to June.